Ressentiment of the Strong and Entitled: A Nietzschean Perspective on the Backlash Against Social Justice - Apostol, Gio Theodore D. (Archīum Ateneo, 2024)
Contemporary discourses often associate group resentment with leftist identity politics. At times, these discourses contain Nietzschean undertones that represent social justice as slave morality. Harold Bloom calls these groups the “Schools of Resentment,” which are comprised of putatively resentful groups such as “Feminists, Afrocentrists, Marxists, Foucault-inspired New Historicists, or Deconstructors.” The assumption that commentators like Bloom make is that these groups, not their opposing counterparts, are resentful. This essay aims to interrogate this assumption and proposes the alternative view that hegemonic groups that social justice movements seek to resist are also susceptible to ressentiment. I argue that the “ressentiment of the strong” is expressed in the contemporary phenomenon of backlash against social justice. The essay makes use of Nietzsche’s theory of the transvaluation of values in the assessment of how resentful groups express ressentiment. I conclude that the ressentiment of the strong initiates a new value reversal: one in which contemporary values of human basic equality are deemed undesirable